Music and Artificial Intelligence - Łukawski, Adam; Music, AI and Blockchain: Decentralized Creativity and Posthuman Agency (doctoral focus session) Orpheus Instituut, Gent December 18-19, 2023; Orpheus Instituut (Ghent, Belgium) (Ghent Orpheus Instituut, 2023)
The goal of this focus session is to equip participants with an understanding of how AI and blockchain technologies are changing society, and how they can augment and redefine creative processes in music. The session will explore the potential of several digital tools for posthuman creative practices, providing insights into emergent modes of artistic creation. More specifically, the session will address topics such as the enhancement of human creativity through AI, effective techniques for investigating music with AI and blockchain, the significance of concepts such as decentralized creativity, posthuman music, hypermusic, Music 2.0, and the role and ownership of art in the posthuman era. Meetings will involve theoretical discussions and practical hands-on experience, such as examples of composing with AI models or creating music NFTs.In this lecture, the topic of Music and Artificial Intelligence (AI) was unfolded from the point of view of a researcher and music composer, introducing topics such as AI-thinking in music, navigating the difference between classical algorithms and AI models, explaining what AI can do in music, presenting various AI tools for music and examples of music created with the use of these technologies.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music